A Portrait of Composer Steven Gellman for His Seventieth Birthday - Prevost, Roxane (Intersections)

(untitled) (Canadian University Music Society / Société de musique des universités canadiennes, 2016)
This article begins with a short biography of and an exchange with Canadian composer Steven Gellman, who celebrated his seventieth birthday in 2017. The biography outlines his life trajectory from a young boy interested in composition to his studies with Messiaen to his career in Canada. The exchange with the composer consists of fourteen questions on Gellman’s creative process and his reflections on his career as a composer.